2010
DOI: 10.1063/1.3275509
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and optical characterization of n-InAsSb/n-GaSb heterojunctions

Abstract: Articles you may be interested inDual-wavelength sensitive AlGaN/GaN metal-insulator-semiconductor-insulator-metal ultraviolet sensor with balanced ultraviolet/visible rejection ratiosWe report the electrical properties of n-InAsSb/n-GaSb heterojunctions as a function of the GaSb doping concentration. Because of the staggered type II band alignment, strong electron accumulation occurs on the InAsSb side. For low GaSb doping, depletion occurs on the GaSb side resulting in a Schottky-like junction as previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…The cut-off wavelength of the photo-response for D2 is 2.1 µm, consistent with photon absorption in the GaSb buffer layer. No photo-response from the InAsSb layer (expected in the 2 to 4 µm wavelength range) could be detected when a negative bias is applied to D2, and this is in good agreement with what reported by Lackner et al [19]. The simulated band diagram in Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The cut-off wavelength of the photo-response for D2 is 2.1 µm, consistent with photon absorption in the GaSb buffer layer. No photo-response from the InAsSb layer (expected in the 2 to 4 µm wavelength range) could be detected when a negative bias is applied to D2, and this is in good agreement with what reported by Lackner et al [19]. The simulated band diagram in Fig.…”
Section: Resultssupporting
confidence: 91%
“…The principle of operation of D2 is therefore analogous to that of a metal semiconductor Schottky photodetector. On the other hand, both Sharabani et al [18] and Lackner et al [19] reported dual-color IR (SWIR and MWIR) detection capability for similar heterostructures to D2 (InAsSb/GaSb detectors) when a positive bias was applied. However, D2 shows no extension of cut-off wavelength for positive voltages up to 0.2 V, beyond which it was not possible to collect spectra due to the high level of dark current.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The doping concentration of the substrate was 1 Â 10 18 cm À3 , which forms a tunnel junction with low n-doped InAsSb, as shown in an earlier work. 21 HR-XRD was employed to verify the layer composition, thickness, and strain state.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In a recent work we showed that the nInAsSb/n-GaSb heterojunction is rectifying for n-GaSb < 5×10 17 cm -3 and increasingly Ohmic above that concentration. [12] This is presumably due to the formation a tunneling junction for higher doping levels. Thus, if a back side contact device is to be used, the doping level in the GaSb side must be at least 10 18 cm -3 .…”
Section: Electrical Properties Of Gasb/inassb Interfacesmentioning
confidence: 99%